Corporate governance and firm performance: empirical evidence from Pakistan. Issue 1 (17th August 2021) - Farooq, Muhammad; Noor, Amna; Ali, Shoukat
Abstract : Purpose: The purpose of this research is to look into the governance–performance relationship in the context of critical firm characteristics, such as firm size. Design/methodology/approach: Based on total assets, sample firms were classified as small or large. The governance index, which is based on 29 governance provisions covering the audit committee, board committee, ownership and compensation structure of the respective firm, measures governance quality among sample firms. A higher governance index indicates a higher level of governance quality and vice versa. Accounting and market value measures are used to determine firm profitability. The authors used the two-stage least square (2SLS) method of estimation of the model to eliminate the simultaneous equation bias. Findings: Corporate governance (CG) appears to have a positive impact on accounting return and market indices (Tobin's Q), but it has little impact on return on equity. In terms of firm size, larger companies profited more from better governance implementation than smaller firms that lacked these principles, thus improving CG. The findings indicate that small businesses should improve their governance mechanisms to reap the benefits of CG in terms of increased profitability. Research limitations/implications: There are certain drawbacks to this research. First, the authors omitted qualitative aspects of CG from the CG index, such as the board's decision-making process, directors' perceptions of the board's position and directors' age and qualifications. Such a qualitative component will improve the governance index in the future while building the governance index. Second, as the current study only looks at the nonfinancial sector, caution should be exercised before applying the findings to the entire population. Practical implications: The findings show that companies that follow good governance standards have better accounting and market efficiency than those that do not. As a result, good governance practices can help firms in developing countries improve their performance. Academic researchers, regulators, investors, lenders and practitioners can find the findings useful in establishing a true relationship between firm performance and CG practices in Pakistan. Originality/value: The relationship between governance and profitability in the context of firm size is examined in this research. Firms with varying resources and ability to implement CG codes have varying effects on profitability. To the authors' knowledge, there was a gap in the literature that addressed this topic in the local context.